Exploring transversal competencies in engineering students through international experiences - Chans, Guillermo M.; Valle-Arce, Ana Paula; Salas-Maxemín, Salvador; Caratozzolo, Patricia; Camacho-Zuñiga, Claudia (Frontiers in Education, 2025)
Well-rounded professionals must have competencies that adapt their expertise to contribute to future advancements. Beyond technical prowess, skills such as critical thinking, teamwork, communication, leadership, management, and entrepreneurship are essential for the modern workforce and solving twenty-first-century problems. Lifelong learning is a fundamental educational principle that prepares individuals to acquire knowledge and skills at any stage. With this interest in mind, higher education institutions pursue abroad study programs to involve students in different learning opportunities. Stepping outside familiar environments immerses individuals in new challenges, fostering a rich learning experience that promotes the development of critical competencies shaped by a global perspective. This research analyzes the competencies students developed according to their educational model and during their experience abroad. Data were collected through a 43-question semi-structured interview with 13 undergraduate engineering students experiencing an abroad study program. Participants conducted a personal assessment to reflect on their enhancement of competencies through personal and academic performance. The analyzed competencies correlate to those defined in the Tec21 Educational Model, a model designed by Tecnologico de Monterrey in 2019, in which the participants of this research are enrolled. The model defines seven competencies that every degree must develop: self-knowledge and management, innovative entrepreneurship, social intelligence, ethical and civic engagement, reasoning for complexity, communication, and digital transformation. Results indicate that the participants mainly developed competencies in reasoning for complexity, social intelligence, and communication. Such skills are essential for tackling global challenges, as they demonstrate the ability to generate creative solutions, communicate ideas effectively, and foster meaningful collaboration. Conversely, the competencies of digital transformation and ethical and civic engagement were less developed. These findings suggest areas for improvement within the Tec21 model, emphasizing the need to cultivate individuals aware of their societal impact and proficient in applying technological tools effectively.